Interpersonal psychotherapy for traumatic grief following a loss due to COVID-19: a case report - Abdul Samad, Farah Deena; Pereira, Xavier Vincent; Chong, Siew Koon; Abdul Latif, Muhammad Hanif Bin (Frontiers in Psychiatry, 2023)
Interpersonal psychotherapy (IPT) is a highly regarded evidence-based psychotherapy that aims to alleviate the suffering of clients and improve their interpersonal functioning.Research has demonstrated the effectiveness of IPT in depressive, bipolar and eating disorders. IPT also focuses on grief and loss as a problem area to help clients address and process their grief symptoms, leading them to reach a phase of finding meaning. However, traumatic grief which is characterized by someone who has both symptoms of trauma and grief can further complicate treatment. As for Posttraumatic Stress Disorder (PTSD), IPT can be a choice of treatment by addressing perceived isolation and emotional dysregulation through mobilizing adequate social support. This case study highlights the efficacy of IPT in treating complicated grief with traumatic experiences caused by the loss of a loved one during the COVID-19 pandemic, without undergoing exposure-based therapy. The treatment course consisted of 12 sessions scheduled twice weekly, and the client received antidepressant medication augmented with antipsychotic medication. After undergoing IPT, the client experienced an improvement in symptoms, gradual recovery of functional disability, and more meaningful interpersonal relationships. The case study presented provides evidence to suggest that IPT is a promising treatment approach for individuals struggling with trauma related to grief.